A technique for using short term soft liners as complete dentures final impression material - Varun Baslas; Saumyendra V. Singh; Himanshi Aggarwal; Simranjeet Kaur; Kamleshwar Singh; Kaushal K. Agarwal (Elsevier, 2014)
Tissue conditioners can be used to condition abused tissues, record functional impressions, make temporary relining for surgical splints and obturators, and for other clinical applications, mainly because of their specific viscoelasticity. Their function in complete denture fabrication is debatable but their use as a functional impression material has been proved. The present article describes a technique for using tissue conditioners as functional impression materials. Correct method of usage, manipulation, specific properties as impression materials and precautions in different situations for obtaining accurate impressions has been highlightened.